Development of an IoT-Based Smart Home Water Leak Detection System - Mohabuth, AQ; Pal, T; Sobrun, M (International Journal of Computer Sciences and Engineering, 2021)
Water is a precious commodity and should not be wasted. It has always been a challenging issue worldwide to prevent wastage of potable water. Inspecting the entire water pipeline system of a house each time to find a leak or issue can be time consuming and costly if water is being wasted for a long period of time. People like to complete their daily household chores without any delay and find it frustrating when their work is halted because of unavailability of water arising from damages in their home water piping system. It is always a headache when there is leakage in the pipe systems at home. People may be away from their home, at work or on vacations. Pipe bursting goes unnoticed and resulted in consequent damages. Smart system can surely be helpful in preventing those unwanted surprises. This paper presents an implementation of a smart home water protection system that proves to be beneficial in saving up water, money and time. The smart system notifies the user about damages in home water pipeline systems while simultaneously taking measures to prevent further losses. Warning messages are issued to people thus keeping them informed about the problematic state of their water pipeline system. Alternatively, the smart system can take actions automatically to temporarily remediate the problem or allow the house owner to do otherwise. The system provides the user with a simple yet intuitive interface where information about the condition of the water pipeline system is in a conclusive way.